From Design to Execution: S-Curve-Controlled Implementation of a Hybrid Urban Drainage System in West Pontianak - Saputra, Doddy Cahyadi; Santosa, Dimas Puji; Sugasta, Hervian Handika; Adibah, Fairuz; Rangga, Boy (Fakultas Teknik Universitas Tanjungpura, 2025)
This study presents an integrated approach to optimizing urban drainage infrastructure in Gg. Smile, West Pontianak